Binary Archetype in Ben Elton’s Novel “Two Brothers” - V. G. Novikova (Научный диалог)
The novel of the modern British writer Ben Elton “Two Brothers” (2012) is analyzed in terms of the functioning of the binary archetype in it. It is noted that contemporary cultural-historical thinking is characterized by a rejection of the classical rational type of thinking based on binary oppositions. The restoration of a certain clear opposition in B. Elton’s novel is interpreted as the author’s desire to preserve the opposition of humanitarian ideology to fascism at the present stage of socio-cultural development. It is established that the artistic structure of the novel clearly correlates with the tradition of twin myths. The author of the article draws attention to the fact that the plot of the novel is connected with the fate of two boys from a Jewish family, one of whom was his own son, and the second, a German by nationality, was adopted. It is emphasized that according to the laws of the twin myth, they conflict among themselves, but this is an imaginary confrontation, because in fact the brothers belong to the world of Germany, which opposed the onslaught of Nazi ideology. It is shown that at the deep level of his work, Ben Elton builds a distinct binary opposition of Good and Evil, in which there can be no justification for chauvinism as an extreme manifestation of fascist doctrine.